Selection of colours and shapes of laser light apparatus for improvement of motorcycle conspicuity - Mustafa Talib Yousif , Ahmad Farhan Mohd Sadullah, Khairil Anwar Abu Kassim , Zaid Abdi Alkareem Alyasseri (International Journal of Advanced Science and Technology, 2020)
Motorcycles, inherently more dangerous than cars, are considered to be one of the extremely vulnerable modes of conveyance. The high risk of multiple motorcycle collisions is usually associated with a low level of motorcycle conspicuity. This paper proposes measures to reduce the motorcycles crashes related to conspicuity by improving motorcycle visibility and increasing the attentiveness of vehicle drivers by using an innovative Laser Light Apparatus (LLA). The objective of this study is to select the efficient colours and shapes of LLA to be equipped onto a motorcycle, to improve the conspicuity at night condition. A method is selected by five industrial and academic experts of industry and professors to determine the most efficient colours and shapes of LLA innovation by means of questionnaire, and experiments conducted on a simulator situation in a night-time like environment at Malaysian Institute of Road Safety Research (MIROS). The results shows that experts choosing 100% green colour as the efficient coloured compared to red and blue wavelengths of Lasers. In terms of the shape, experts choose a 100% locator shape as a better than dot and liner. The findings of this study can be useful to enhance motorcycle visibility, thereby reducing accidents related to lack of conspicuity.